MODEL DISCOVERY LEARNING DENGAN PENDEKATAN SAINTIFIK BERMUATAN KARAKTER UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF - Hendra Erik Rudyanto (Universitas PGRI Madiun, 2014)
This Study aims to produce a model learning device discovery learning with scientific approach to improve the character charged valid creative thinking, practical and effective. The model refers to a model of learning development includes activities Plomp initial investigation, design, realization/contruction, testing, evaluation and revision. The results showed that (1) learning tools developed valid; syllabus ehit an average of 3,3 (very good); RPP with an average of 3,2 (good); LKS with an average of 3,2 (good); textbook student with an average of 3,3 (very good); and TKBK with an average of 3,5 (good).; (2) the stated learning practical , namely: 1) the activity of student on both criteria, an average score 74,1%; 2) the activity of the teacher are very good on the criterion, the average score of 98,25; 3) positive teacher response, a score of 97,14; 4) positive students response, average 89,73.; (3) the learning of mathematics is declared effective the indicator 1) traffic to think creatively achieve mastery with the average value of 71,55 and a classical completeness reaches 90%; 2) the average grade of creative thinking ability model of discovery learning with scientific approachis better than ekspositori class; 3) the character of the curiosity and skills to communicate a positive influence on the ability to think creatively; and 4) an increase in the ability to think creatively in class models discovery learning with scientific approach. Keywords: discovery learning, scientific approach, creative thinking ability.